2013
DOI: 10.3109/08820538.2013.810286
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive Keratectomy on Purely Refractive Accommodative Esotropia

Abstract: A two-year follow-up showed that photorefractive keratectomy was an effective treatment for esotropia associated with mild to moderate hyperopia in young adults with purely refractive accommodative esotropia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Twenty-one case series enrolling adult patients were included in this review, out of which 8 were prospective [5, 28, 35, 38, 41, 42, 44, 45]. A total of 289 patients (577 eyes) were recruited with an age range of 15–52 years.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-one case series enrolling adult patients were included in this review, out of which 8 were prospective [5, 28, 35, 38, 41, 42, 44, 45]. A total of 289 patients (577 eyes) were recruited with an age range of 15–52 years.…”
Section: Resultsmentioning
confidence: 99%
“…PRK was the technique of choice in 7 studies [30, 31, 38, 40, 44, 46, 47], LASIK was performed in 8 studies [5, 19, 28, 29, 32, 34, 39, 41], LASEK was reported in 1 study [5] and 3 studies implanted IOLs, including iris-fixated [36, 41] and implantable collamer lens [45]. In 3 studies [35, 37, 43], both PRK and LASIK were used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations